2017
DOI: 10.1158/2326-6066.cir-17-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Effects of Vaccine-Activated CD8+ T Cells Associate with Weak TCR Signaling and Induction of Stem-Like Memory T Cells

Abstract: To understand why vaccine-activated tumor-specific T cells often fail to generate antitumor effects, we studied two α-fetoprotein–specific CD8+ T cells (Tet499 and Tet212) that had different antitumor effects. We found that Tet499 required high antigen doses for re-activation, but could survive persistent antigen stimulation and maintain their effector functions. In contrast, Tet212 had a low threshold of re-activation, but underwent exhaustion and apoptosis in the presence of persistent antigen. In vivo, Tet4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…On the other hand, we found that stemlike memory T cells with naive-like phenotype generated a better antigen response in vivo. (46) In the current study, we found that a significant portion of TCR-T cells were of naive-like phenotype (CD45RA 1 CD62L 1 ) in NSG mice. Whether the CD45RA 1 CD62L 1 cells are more responsive to antigen and thus generate a better antitumor effect on TCR-T cells remains to be studied.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…On the other hand, we found that stemlike memory T cells with naive-like phenotype generated a better antigen response in vivo. (46) In the current study, we found that a significant portion of TCR-T cells were of naive-like phenotype (CD45RA 1 CD62L 1 ) in NSG mice. Whether the CD45RA 1 CD62L 1 cells are more responsive to antigen and thus generate a better antitumor effect on TCR-T cells remains to be studied.…”
Section: Discussionsupporting
confidence: 50%
“…One recent study found the CD26 hi T cells were more persistent after transfer and generated a potent antitumor effect, which may be the better T‐cell subset for TCR engineering. On the other hand, we found that stem‐like memory T cells with naive‐like phenotype generated a better antigen response in vivo . In the current study, we found that a significant portion of TCR‐T cells were of naive‐like phenotype (CD45RA + CD62L + ) in NSG mice.…”
Section: Discussionsupporting
confidence: 43%
“…Furthermore, human studies utilizes non-specific, polyclonal T cell activation to generate T cell grafts for ACT, whereas we investigated antigen-specific CD8 + T cell activation in our study. As TCR affinity affects the ability of CD8 + T cells to differentiate into T scm cells, our results might be influenced by our TCR transgenic model [26]. Lastly, JQ1 improved both CD8 + and CD4 + T cell function and engraftment [15], whereas our model is limited to the study of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 95%
“…The TCR repertoire of naturally primed CD8 + T cells includes mostly TCRs with medium to low affinity, some of which are cross-reactive to autoantigens [32]. Nevertheless, lower affinity TCR may facilitate the priming of long lasting immune memory [33], including stem cells like memory T cells (Tscm). Mysteriously, natural TIL therapy seemed only succeeding in controlling melanoma and Hodgkin's disease but failed in other tumor types with identifiable tumor-associated antigens [34].…”
Section: The Tumor-antigen Specificity and Mutationmentioning
confidence: 99%
“…It seems to be that the efficacy of initial tumor control by ACT is associated with high-affinity T cell engraftment, but this may not be true if a long-lasting antitumor T cell persistence is required. Low affinity T cells with the capability becoming stem memory T cells (Tscm) were reported to produce better and long lasting protective effects in mouse model of HCC [33]. Generating long lasting memory T cells including Tscm probably is the holy grail of ACT to reach the goal of long lasting tumor control or eradication.…”
Section: The Influence Of Immunosuppressive Tumor Microenvironment (Tmentioning
confidence: 99%